Communicating the complex lives of families that include a child with Down syndrome. Issue 1 (2nd January 2023) - Cooke, Emma; Coles, Laetitia; Staton, Sally; Thorpe, Karen; Chawla, Jasneek
ABSTRACT: Families of children with Down syndrome experience complex lives and needs, yet the few existing studies on these families are written in conventional academic prose that is not optimal for knowledge translation beyond academia, particularly for busy healthcare professionals. In this paper, we Depart Radically in Academic Writing (DRAW) (Mackinlay, 2022) and present data poetry and two case studies that draw upon semi-structured interviews with mothers, fathers, and siblings, who were interviewed separately about their experiences of having a child/sibling with Down syndrome. We introduce our interdisciplinary team that includes academics and clinicians to contextualise our focus on research translation. We demonstrate that writing with creative criticality (i.e. 'DRAWing') contributes an embodied and affective understanding of research participants' stories, which is largely lacking in the academic literature on families of children with Down syndrome and the sociology of health and illness field more broadly. Moreover, DRAWing can impact audiences emotionally as well as intellectually (Richardson, 2003, p. 924), which has important knowledge translation implications for both healthcare professionals and these families. DRAWing can capture healthcare professionals' attention, prompting them to critically reflect on their practices and opportunities for improving care and treatment for these families.